Doses of hepatitis B revaccination needed for the seronegative youths to be seropositive to antibody against hepatitis B surface antigen. (3rd August 2019) - Jan, Chyi-Feng; Liu, Tzu-Hung; Ho, Chien-Han; Chien, Yin-Chu; Chang, Che-Jui; Guo, Fei-Ran; Huang, Kuo-Chin
Abstract: Objectives: To determine the required hepatitis B vaccine doses for subjects who were seronegative for three hepatitis B seromarkers during their youth who wish to have seroprotective antibodies against the hepatitis B surface antigen (anti-HBs). Methods: We conducted a retrospective cohort study. From 2012 to 2015, graduate school students born after 1986 who were seronegative for three hepatitis B virus seromarkers at college entrance ( n = 1037) were recruited. Four groups of subjects received zero to three doses of a hepatitis B vaccine booster at their free willingness, and their anti-HBs titre were measured at their graduate school entrance. Very low and extremely low antibody titres against the hepatitis B surface antigen were elucidated by graphic inference to determine the required booster dose cut-off value for seropositivity after revaccination. Results: The anti-HBs seropositive rates in the four groups of subjects receiving the hepatitis B booster vaccine(s) were 17.7%, 52.1%, 78.6% and 90.9% for those receiving zero, one, two and three doses, respectively. In subjects with very low antibody titres against the hepatitis B surface antigen after one dose of the vaccine booster and subjects with an extremely low titre after two doses of the booster, the seropositive rates reached 95% at the cut-off value of 3 mIU/ml. Conclusion: A seropositive rate of at least 95% can be reached by the administration of two hepatitis B booster doses to youths with extremely low antibody titres against the hepatitis B surface antigen (<3 mIU/ml) and administering one dose to those with very low titres (3–10 mIU/ml) at college.